INFORMATION MARKETING IN SRI LANKAN ACADEMIC LIBRARIES - Jayatissa, Block; N.N., Edzan (Malaysian Journal of Library and Information Science, 2002)
Describes a study that investigates the marketing of â€œfree-basedâ€ information services in five selected academic libraries in Sri Lanka. A total of 5 senior librarians were interviewed and 250 library users answered questionaires.The study revealed that all the academic libraries offer free information services to their clients with the exception of photocopying and document-delivery services.The academic libraries should aggressively market their services/products and must move from the provision of traditional library services(book loans) to a more IT based information services(Internet).